Rancang Bangun Service Oriented Architecture (SOA) Pada SMKN 1 Selong - Qori' Rahmawati Pertiwi; Royana Afwani; Sri Endang Anjarwani (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2020)
In an organization, the development of a system cannot be done as a whole but is done in stages, This is caused by organizational needs that are always changing from time to time. Also, in an organization, there is a lot of data or information that is done together, where one data can be used by several fields and one data can also be used for many functions. Similar to SMK 1 Selong, the same data or information can be used by several midwives and can be used for many functions. To overcome these problems in this study carried out the design and construction of Service Oriented Architecture (SOA). SOA is software development with a service approach. In SOA the data needed for the development of a system is defined from the start to facilitate the development of a continuous system and can facilitate if there is a change in data because SOA provides the ease of integration of several different systems. In this research the SOA analysis and design process at SMK 1 Selong has been carried out and 9 services are obtained: student service, employee service, service teacher, service value, financial service, curriculum service, library service, service facilities and infrastructure, and service administrator. These services are implemented using web service technology with a codeigniter framework